Urban variability in Recife - PE, through contributions: precipitation, temperature and relative air humidity (Research, Society and Development, 2022)
The objective of this study is to study urban variability, through the contributions of pluviometric indices, temperatures and relative humidity, comparing the periods 1931-1960; 1961-1990 and 1991-2016 for precipitation and the 1962-1990 and 1991-2016 periods for temperature and relative humidity of the 1931-2016 and 1962-2016 averages respectively, attempting to quantify climate change and to identify the Influence of large-scale El Niño events, aiming to contribute to the managers responsible for urban planning and improving the quality of life of the inhabitants and the ecosystem. Rainfall, temperature and humidity data were used by the National Institute of Meteorology (INMET). Basic statistical parameters were calculated as well as variations of the annual anomalies in order to identify buoyancy in the data and the influence of extreme events. These fluctuations in the pluviometric indices registered in the periods of 1931-1960; 1961-1990 and 1991-2016 may be related to the following factors or facts: The expansion of the municipality both vertically and horizontally; The exchange of the place of the rain gauge from the urban area to near the zone of the forest and near the river; And due to urban afforestation. The city of Recife suffered from disorderly growth, with no specific patterns of planning in urbanization that caused variations in the microclimate of the urbis, causing thermal discomfort and reducing the quality of life of its inhabitants. There is an intense flow of automotive vehicles and people throughout the day due to activities related to work, commerce and services, as well as the concentration of various buildings, waterproofed areas as well as buildings making circulation of local air difficult. It is suggested an increase of green areas interbairros from the afforestation that has been shown as an alternative for the improvement of the quality of life in urban spaces.